Risk of Depression among Early Onset Type 2 Diabetes Mellitus Patients - Baizid Khoorshid Riaz; Shahjada Selim; Megan Neo; Md Nazmul Karim; M. Mostafa Zaman (Dubai Diabetes and Endocrinology Journal)
Methodology: Biochemically confirmed type 2 diabetes mellitus (T2DM) patients (n = 1,114) were recruited from the outpatient department of 2 tertiary care hospitals in Dhaka, Bangladesh. Face-to-face interview was conducted using a semi-structured questionnaire containing sociodemographic parameters and relevant information about depression and diabetes. Biochemical test results and treatment-related information were taken from patients’ records. The Hospital Anxiety and Depression Scale (HADS) was used to screen all patients for psychiatric manifestation. Those diagnosed by HADS were subsequently reassessed using structured clinical interview for DSM-5 Disorders – Clinician Version. T2DM diagnosed at age <40 years were considered as early onset T2DM. Association between age of onset category and depression was assessed using multivariable mixed-effect logistic regression adjusting for random variation of the area of residence and plausible confounders. Results: Around a third of the participants (32.5%) were diagnosed with T2DM before the age of 40 years. Early onset T2DM patients were found to have 57% increase in the risk of developing depression (OR 1.57; 95% CI 1.13–2.28; p = 0.011) in comparison to those with usual onset T2DM (≥40 years). Among other factors a positive family history for diabetes (OR 1.33; 95% CI 1.03–1.78; p = 0.038), poor glycemic control (OR 1.31; 95% CI 1.03–1.68; p = 0.028), presence of 1, or more diabetic complications (OR 1.37; 95% CI 1.03–1.78; p = 0.011) also showed increased risk of depression. Conclusion: Early onset T2DM patients are at greater risk of developing depression. The finding is likely to help in setting preventive strategies aiming to reduce the presence of concomitant depression symptoms among diabetes.